A Neuroscience Review of the Letter of Ali Imran 190-191 - Sena Sena (Edumaspul: Jurnal Pendidikan, 2024)
Humans have advantages when compared to other creatures, namely being able to use their minds. Like other creatures, Allah has also given them minds. Mind which comes from the word 'aqala ya'qilu 'aqlan can be called neuroscience. In the review of philosophical science, humans are thinking animals (hayawanun natiq), where by Allah ASWT humans are given a special task as khalifah fil ardh to manage and prosper this earth. This task as a khalifah requires sufficient knowledge, must have a smart brain or really optimize their intellectual abilities as best they can and like to contemplate Allah's creations in this universe. As Allah says in the Qur'an Surah Ali Imran [3]: 190-191, "Indeed, in the creation of the heavens and the earth, the alternation of day and night there are signs of Allah's greatness for people who have reason. Namely, those who remember Allah standing, sitting and lying down, and they think about the creation of the heavens and the earth. " In addition to discussing the brain or reason, it also shows its relationship with verses ending in, "afalaa ta'qiluun" and verses ending in, "Afalaa yatadzakkaruun". This article examines the relationship between neuroscience and the Qur'an and efforts to study neuroscience in optimizing humans in using their brains. The research method used is qualitative research with a literature study approach. This study aims to examine the relationship between neuroscience and the Qur'an and the extent to which neuroscience plays a role in optimizing the human brain to be optimal in carrying out its duties as a caliph on earth.